MODEL SINGLE EXPONENTIAL SMOOTHING UNTUK MEMPREDIKSI JUMLAH PESERTA DIDIK BARU DI SMPN 1 BATAUGA - Henny Hamsinar; Fithriah Musadat; Hasmiati Ibrahim (Prodi Teknik Informatika Unidayan Baubau, 2022)
Acceptance of new students, known as Penerimaan Peserta Didik Baru (PPDB), is an annual education unit agenda. Predicting the number of new students is needed in school management planning activities. This study aims to predict the number of new students at SMPN 1 Batauga in 2022. The data used is data from the last 5 years. 2017 to 2021. The Single Exponential Smoothing method is used to make predictions using parameters α=0.1 to α=0.9. From the prediction results, it is obtained that the alpha value has the smallest error value, namely alpha=0.9 and MAPE of 20%. So that the number of students at SMPN 1 Batauga in 2022 is 114 people.